Ethnomedicinal survey and scientific validation of inflammation-healing plants used by the Tengger community in East Java, Indonesia - WEKA SIDHA BHAGAWAN; WIWIED EKASARI; MANGESTUTI AGIL (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Bhagawan WS, Ekasari W, Agil M. 2025. Ethnomedicinal survey and scientific validation of inflammation-healing plants used by the Tengger community in East Java, Indonesia. Biodiversitas 26: 3160-3173. This study investigates the profound ethnomedicinal knowledge of the Tengger community in East Java, Indonesia, with a specific focus on plant species traditionally used to manage inflammation and pain-related conditions. The primary objective was to meticulously document the medicinal plants utilized by the community and assess their pharmacological relevance through literature-based validation. Data were obtained through semi-structured interviews and in-depth observations with selected informants, using a snowball sampling technique. Quantitative indices (species use value, family use value, fidelity level, and informant consensus factor) were applied to evaluate each species' cultural and therapeutic significance. A total of 82 plant species belonging to 42 families were identified and utilized in various preparations to treat 15 inflammation and pain-related disorders. Notably, 4 of the 6 plant species with the highest species use value have been scientifically validated for their anti-inflammatory and analgesic activities, providing a solid foundation for the community's traditional knowledge. However, the pharmacological properties of Borreria laevis and Elaeocarpus longifolius remain unexplored. The enduring use of these medicinal plants is a testament to the community's rich ethnomedical tradition, and further pharmacological investigations may lead to the discovery of new therapeutic agents for treating inflammation and pain.